2013
DOI: 10.1039/c3cp51112j
|View full text |Cite
|
Sign up to set email alerts
|

Rechargeability of Li–air cathodes pre-filled with discharge products using an ether-based electrolyte solution: implications for cycle-life of Li–air cells

Abstract: The instability of currently used electrolyte solutions and of the carbon support during charge-discharge in non-aqueous lithium-oxygen cells can lead to discharge products other than the desired Li2O2, such as Li2CO3, which is believed to reduce cycle-life. Similarly, discharge in an O2 atmosphere which contains H2O and CO2 impurities would lead to LiOH and Li2CO3 discharge products. In this work we therefore investigate the rechargeability of model cathodes pre-filled with four possible Li-air cell discharge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

31
238
1
6

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 199 publications
(291 citation statements)
references
References 40 publications
31
238
1
6
Order By: Relevance
“…The slight deviation downwards from the 1 e − /CO 2 line can be explained by two effects: i) the lithium oxalate used here contains about 1% Li 2 CO 3 as impurity, whose oxidation also gives CO 2 , but in a ≥ 2 e − /CO 2 process; 29 and ii) about 2.5% of the total CO 2 remain dissolved in the electrolyte solution and are thus not detectable by OEMS (for details see Discussion section of this paper).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The slight deviation downwards from the 1 e − /CO 2 line can be explained by two effects: i) the lithium oxalate used here contains about 1% Li 2 CO 3 as impurity, whose oxidation also gives CO 2 , but in a ≥ 2 e − /CO 2 process; 29 and ii) about 2.5% of the total CO 2 remain dissolved in the electrolyte solution and are thus not detectable by OEMS (for details see Discussion section of this paper).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we fabricated model electrodes that contain only lithium oxalate in a conductive carbon matrix, similar to the ones used by Meini et al, 29,30 who studied the anodic decomposition of lithium salts (Li 2 O 2 , Li 2 CO 3 , LiOH, and Li 2 O). Figure 1a shows the potential during the galvanostatic charge of an electrode consisting of 45 wt% sub-micron lithium oxalate, 45 wt% carbon black and 10 wt% binder, with a nominal rate of C/10 (based on its theoretical decomposition capacity of 525 mAh/g LO ; see reaction 1 below).…”
Section: Resultsmentioning
confidence: 99%
“…While it is clear that Li 2 CO 3 decomposition evolves CO 2 , the fate of the third O atom in CO 3 2− has been an enduring open question since no O 2 evolves, although this would be expected from the formal oxidation reaction:3e, 4c,4f–4h,4j, 5b true20.166667emLi2CO340.166667emLi++40.166667emnormale-+20.166667emCO2+normalO24ptE=3.820.166667emnormalV4ptvs.4ptLi/Li+ …”
mentioning
confidence: 99%
“…In analogy to carbonate oxidation in aqueous media,13 it has been suggested that Li peroxodicarbonate (LiO 2 COOCO 2 Li) forms as an intermediate 4h. Such an intermediate has been questioned on the basis that 1) CO 3 2− is poorly soluble and would thus lack mobility to combine to peroxodicarbonate and 2) the high charge density of the peroxodicarbonate anion ( − O 2 COOCO 2 − ) would not allow O−O bond formation or would lead to immediate bond cleavage 4c, 14. However, neither large carbonate mobility nor dissociation are required and a mechanism via a peroxodicarbonate intermediate can be proposed (Figure S8a) and rationalized based on previous reports 4i, 15.…”
mentioning
confidence: 99%
“…Li 2 O 2 is the only discharge product that has been confirmed to return O 2 during oxidation. 40 However, as the charge overpotential increases, O 2 evolution gradually drops < 2e − /O 2 , clearly demonstrating the presence of side-reactions during the whole charge process. The OEMS data largely agrees with observations of McCloskey et al .…”
mentioning
confidence: 99%